A coarse aggregate ultra-high performance concrete and its preparation method and application

By introducing coarse aggregate with optimized mix ratio into ultra-high performance concrete, a tight packing system is formed, which solves the problems of low elastic modulus and flexural tensile strength caused by the removal of coarse aggregate in the prior art, and achieves high compressive strength and concrete with high fracture toughness.

CN118771823BActive Publication Date: 2025-01-07THE FIRST ENGINEERING COMPANY OF CCCC FOURTH HARBOUR ENGINEERING CO LTD +2
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411024581.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-29
Publication Date
2025-01-07
Estimated Expiration
2044-07-29

AI Technical Summary

Technical Problem

After removing the coarse aggregate, the amount of gelling material is used too high, resulting in low elastic modulus, initial crack tensile strength, flexural tensile strength and fracture toughness.

Method used

By introducing coarse aggregates with optimized mix ratios, including large, medium and small particles, and combining gelling materials and other components, the particle size relationship and component ratio are optimized to form a tight packing system and improve the elastic mold of concrete. Quantity, initial crack tensile strength, bending tensile strength and fracture toughness.

Benefits of technology

On the basis of maintaining high compressive strength, the elastic modulus, initial crack tensile strength, flexural tensile strength and fracture toughness of concrete are significantly improved, meeting the UHPC minimum compressive strength standards in most countries, and reducing gelling materials Dosage.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118771823B_ABST
    Figure CN118771823B_ABST
Patent Text Reader

Abstract

The invention discloses a coarse aggregate ultra-high performance concrete, belonging to the technical field of concrete. The coarse aggregate ultra-high performance concrete of the invention comprises 600-1000 parts of cement, 100-300 parts of silica fume, 100-200 parts of mineral admixture, 10-50 parts of water reducer, 600-1000 parts of fine aggregate, 200-600 parts of coarse aggregate, 50-200 parts of steel fiber and 100-200 parts of water; the coarse aggregate is composed of a large amount of steel fiber with a mass ratio of (8-10): (2-3): 1 The present invention reduces the amount of cementitious material in concrete by reintroducing coarse aggregate into the ultra-high performance concrete system, thereby minimizing the influence of coarse aggregate on the densest packing of original ultra-high performance concrete, so that the elastic modulus, initial crack flexural strength, flexural tensile strength and fracture toughness of the concrete are improved while maintaining the original ultra-high compressive strength.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of concrete, and in particular to a coarse aggregate ultra-high performance concrete and a preparation method and application thereof. Background Art

[0002] Concrete is an artificial stone made of cementitious materials, aggregates and water in a certain proportion, which is formed by mixing and vibrating and cured under certain conditions. It is one of the most important civil engineering materials in contemporary times. Concrete materials have a wide range of sources, a large adjustable range of performance, good shaping before hardening, simple and variable construction processes, and can be reinforced with steel bars. This makes concrete widely used in civil engineering and concrete technology has developed rapidly. According to statistics, before the 1970s, the average strength of concrete was about 25MPa, but in actual projects today, concrete above C80 has begun to be promoted and applied. The highest strength of Norway's concrete technical standard (NS3473E) has reached C105, and the highest strength in the "Guide to High-Strength Concrete" issued by the German Concrete Association in 1995 is C105. It has also reached C115. In 1994, based on the theory of the most dense packing method, the concept of ultra-high performance concrete (UHPC) was first proposed. Its principle is: adding active mineral admixtures with extremely small particles, removing coarse aggregates with larger particles, making the particle size distribution of the materials in the whole system continuous and uniform, theoretically achieving the most dense packing of all materials, so that the pores between the materials are filled to the maximum, adding fine steel fibers to increase toughness, using high-efficiency water reducers to reduce the water-cement ratio, and using pressurized steam curing methods. Through these measures, the mechanical and durability properties of UHPC have been greatly improved. However, due to the removal of coarse aggregates in the ultra-high performance concrete system, the amount of cementitious materials is too high and the elastic modulus, initial crack flexural strength, flexural strength and fracture toughness are low. Summary of the invention

[0003] In order to overcome the shortcomings of the above-mentioned prior art, the present invention provides a coarse aggregate ultra-high performance concrete (CA-UHPC), which introduces coarse aggregate back into UHPC, optimizes the mix ratio of coarse aggregate, and combines it with cementitious materials and other components. On the basis of the high compressive strength of UHPC, the elastic modulus, first crack flexural strength, flexural strength and fracture toughness of concrete are further improved.

[0004] The technical scheme for achieving the purpose of the present invention is as follows: A coarse aggregate ultra-high performance concrete, comprising, by weight, 600-1000 parts of cement, 100-300 parts of silica fume, 100-200 parts of mineral admixture, 10-50 parts of water reducer, 600-1000 parts of fine aggregate, 200-600 parts of coarse aggregate, 50-200 parts of steel fiber, and 100-200 parts of water; the coarse aggregate is composed of large coarse aggregate, medium coarse aggregate, and small coarse aggregate in a mass ratio of (8-10):(2-3):1, and the particle sizes of the large coarse aggregate, the medium coarse aggregate, and the small coarse aggregate satisfy the relationship:

[0005]

[0006] Where: a is the particle size of large coarse aggregate, in mm;

[0007] b is the particle size of medium coarse aggregate, in mm;

[0008] c is the particle size of small coarse aggregate, in mm;

[0009] n∈[3,4], and a>b>c≥5.

[0010] Referring to the most compact packing theory of UHPC, this scheme combines large-particle coarse aggregate, medium-particle coarse aggregate and small-particle coarse aggregate, and through a large number of tests, summarizes the particle size relationship between large, medium and small coarse aggregates. Experiments have shown that when the particle size of coarse aggregate used in concrete satisfies the above relationship, its packing system is the most compact, meeting the requirements of high compressive strength, high elastic modulus and high splitting tensile strength.

[0011] Specifically, the particle size a of the large-particle coarse aggregate can be selected from 25-40 mm, the particle size b of the medium-particle coarse aggregate can be selected from 10-15 mm, and the particle size c of the small-particle coarse aggregate can be selected from 5-10 mm. Preferably, a∈[29, 34], b∈[10, 12], and c∈[5, 6].

[0012] Preferably, the coarse aggregate is 300-400 parts.

[0013] Preferably, the fine aggregate is selected from at least one of river sand, quartz sand and machine-made sand, and the fineness modulus of the fine aggregate is 2.8 to 1.6. More preferably, the fineness modulus of the fine aggregate is 2.2 to 1.6.

[0014] Preferably, the water-binder ratio of the coarse aggregate ultra-high performance concrete is ≤0.2. Further preferably, the water-binder ratio of the coarse aggregate ultra-high performance concrete is 0.1-0.18.

[0015] Preferably, the coarse aggregate is at least one of diabase crushed stone and basalt crushed stone, the mud content of the coarse aggregate is ≤0.1%, and the apparent density is greater than 2600kg / m 3 .

[0016] Further preferably, the coarse aggregate is diabase crushed stone.

[0017] Preferably, the silica ash is at least one of fully-densified silica ash, semi-densified silica ash and original ash, and the SiO2 content in the silica ash is ≥94%.

[0018] Preferably, the silica fume is compounded by semi-densified silica fume and original silica fume in a mass ratio of 1:(1-3).

[0019] Preferably, the water reducer is selected from at least one of naphthalenesulfonate water reducer, aminosulfonate water reducer and polycarboxylate water reducer; the steel fiber is selected from at least one of straight steel fiber, end-shaped steel fiber and corrugated steel fiber. The cement is selected from at least one of silicate cement, ordinary silicate cement, slag silicate cement, pozzolanic silicate cement and fly ash silicate cement; the mineral admixture is selected from Subot's -HDC(V)UHPC, -HDC(VIII), -At least one of HDC(Ⅱ).

[0020] The present invention also protects a method for preparing the coarse aggregate ultra-high performance concrete, comprising the following steps: mixing cement, silica fume, fine aggregate and coarse aggregate, stirring for 1 to 5 minutes, adding water, stirring for 2 to 5 minutes, adding a water reducer, continuing to stir for 2 to 10 minutes, slowly adding steel fiber, continuing to stir for 2 to 10 minutes, and discharging.

[0021] The present invention also protects the application of the coarse aggregate ultra-high performance concrete in bridges and high-rise buildings.

[0022] Beneficial Effects

[0023] The present invention provides a coarse aggregate ultra-high performance concrete, which reduces the amount of cementitious materials in the concrete by reintroducing coarse aggregate into the ultra-high performance concrete system, screens coarse aggregates of different particle sizes, large, medium and small, and their mix ratios, and summarizes an empirical formula for the optimization design of the mix ratios of large, medium and small particle sizes of coarse aggregates. The packing density of the coarse aggregate ultra-high performance concrete can be greatly improved, and the influence of the coarse aggregate on the densest packing of the original ultra-high performance concrete can be minimized, so that the elastic modulus, the initial crack flexural strength, the flexural tensile strength and the fracture toughness of the concrete are improved while maintaining the original ultra-high compressive strength. DETAILED DESCRIPTION

[0024] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0025] In the examples, the experimental methods used are conventional methods unless otherwise specified, and the materials, reagents, etc. used are all commercially available unless otherwise specified.

[0026] The raw materials used in the embodiments and comparative examples are described as follows:

[0027] Coarse aggregate: diabase crushed stone, produced in Liuzhou City, Guangxi, product specifications include crushed stone (5-10mm), crushed stone (10-20mm), crushed stone (10-30mm), crushed stone (20-40mm), crushed stone (40-80mm), after purchase, further screening to obtain coarse aggregate 1~9:

[0028] Coarse aggregate 1: The particle size of large-particle crushed stone is 29 mm, the particle size of medium-particle crushed stone is 10 mm, and the particle size of small-particle crushed stone is 5 mm;

[0029] Coarse aggregate 2: The particle size of large-particle crushed stone is 40 mm, the particle size of medium-particle crushed stone is 15 mm, and the particle size of small-particle crushed stone is 10 mm;

[0030] Coarse aggregate 3: The particle size of large-particle crushed stone is 34 mm, the particle size of medium-particle crushed stone is 12 mm, and the particle size of small-particle crushed stone is 6 mm;

[0031] Coarse aggregate 4: The particle size of large-particle crushed stone is 37 mm, the particle size of medium-particle crushed stone is 13 mm, and the particle size of small-particle crushed stone is 7 mm;

[0032] Coarse aggregate 5: The particle size of large-particle crushed stone is 20 mm, the particle size of medium-particle crushed stone is 10 mm, and the particle size of small-particle crushed stone is 5 mm;

[0033] Coarse aggregate 6: The particle size of large-particle crushed stone is 45 mm, the particle size of medium-particle crushed stone is 15 mm, and the particle size of small-particle crushed stone is 10 mm;

[0034] Coarse aggregate 7: single-graded diabase, particle size 5 mm;

[0035] Coarse aggregate 8: single-graded diabase, particle size 10 mm;

[0036] Coarse aggregate 9: single-graded diabase, particle size 29 mm;

[0037] Coarse aggregate 10: Granite crushed stone, produced along the West River in Guangdong, with product specifications of large crushed stone (10-30mm), small crushed stone (10-30mm), and crushed stone (10-20mm); after further crushing and screening after purchase, the final particle size distribution is large-particle crushed stone with a particle size of 29mm, medium-particle crushed stone with a particle size of 10mm, and small-particle crushed stone with a particle size of 5mm;

[0038] Cement: Portland cement, PII 52.5R, produced by Zhujiang Cement Plant;

[0039] Silica fume 1: semi-densified silica fume, SiO2 content 96%, purchased from Sichuan Ewende, 960U;

[0040] Silica fume 2: original ash, SiO2 content 94%, purchased from Sichuan Ewende, 940UU;

[0041] Fine aggregate 1: machine-made sand, fineness modulus 2.2-1.6, produced in Jiangmen, Guangdong, after purchase, through standard sieve to remove oversized particles;

[0042] Fine aggregate 2: machine-made sand, fineness modulus 2.8, produced in Jiangmen, Guangdong;

[0043] Mineral admixtures: -HDC(V)UHPC, purchased from Jiangsu Subot;

[0044] Steel fiber: end hook type steel fiber, SF100 / 60BP, purchased from Bolpais;

[0045] Water reducing agent: polycarboxylic acid water reducing agent, -IV, purchased from Jiangsu Subot;

[0046] Water: Guangzhou tap water, in line with the requirements of the standard "Mixing Water for Concrete" (JGJ 63-2006).

[0047] Unless otherwise specified, the components and raw materials used in the embodiments and comparative examples of the present invention are all commercially available raw materials, and the components and raw materials used in each parallel experiment are all of the same kind.

[0048] Examples 1 to 19

[0049] A coarse aggregate ultra-high performance concrete, the preparation method of which comprises the following steps: mixing cement, silica fume, fine aggregate and coarse aggregate according to a proportion, stirring for 2 minutes, adding water and a water reducing agent, continuing to stir for 4 minutes, slowly adding steel fiber and continuing to stir for 2 minutes, discharging the material, molding it in a mold of corresponding size, vibrating and compacting it into a shape, and demolding it after standard curing for 24 hours.

[0050] Table 1 Example coarse aggregate ultra-high performance concrete formula (weight parts)

[0051]

[0052] Table 1

[0053]

[0054]

[0055] Comparative Examples 1 to 8

[0056] The preparation methods of Comparative Examples 1 to 8 are the same as those of Examples 1 to 19.

[0057] Table 2 Comparative Example Coarse Aggregate Ultra-High Performance Concrete Formula (parts by weight)

[0058]

[0059] A coarse aggregate ultra-high performance concrete prepared in Example 1-19 and Comparative Example 1-8 was demolded and placed in 90°C hot water for curing for 3 days, and then placed in 20°C standard curing for 24 hours, and then the following performance tests were performed. The results are shown in Table 3.

[0060] 1. Compressive strength: The specimen size is 100mm×100mm×10mm, and the test is carried out in accordance with the relevant provisions of standard GB / T50081-2019;

[0061] 2. Elastic modulus: The specimen size is 100mm×100mm×300mm, and the test is carried out in accordance with the relevant provisions of standard GB / T50081-2019;

[0062] 3. Initial crack flexural tensile strength: The specimen size is 200mm×200mm×1000mm. The prefabricated cracks are generated by pre-embedded steel plates. The crack length is controlled at 80mm±2mm. The test is carried out using the three-point method in accordance with ISO 14704-2016.

[0063] 4. Flexural tensile strength: The specimen size is 200mm×200mm×1000mm, and the test is carried out using the three-point method in accordance with standard ISO 14704-2016;

[0064] 5. Fracture toughness: The specimen size is 200mm×200mm×1000mm. The prefabricated cracks are generated by pre-embedded steel plates. The crack length is controlled at 80mm±2mm. The test is carried out using the three-point method in accordance with standard DL / T 5332-2005.

[0065] Table 3 Performance test results of embodiments and comparative examples

[0066]

[0067]

[0068] It can be seen from the results of the embodiments and comparative examples that the present invention optimizes the mix ratio design of coarse aggregate and re-adds coarse aggregate to the UHPC system to obtain concrete with high compressive strength, high elastic modulus, high first crack flexural strength, high flexural tensile strength and high fracture toughness, wherein the compressive strength is ≥160MPa, the elastic modulus is ≥50GPa, the first crack flexural tensile strength is ≥11.8MPa, the flexural tensile strength is ≥25MPa, and the fracture toughness is ≥22KJ / m 2 , meeting the standards of most countries regarding UHPC minimum compressive strength greater than 150MPa.

[0069] It can be seen from Examples 3-6 and Comparative Examples 1-2 that when the average size of large, medium and small particles of coarse aggregate does not meet the mix design, the concrete will have a large porosity and uneven distribution, thereby affecting the compressive strength, elastic modulus, first crack flexural strength, flexural strength and fracture toughness.

[0070] It can be seen from Examples 3 and 10 that diabase crushed stone has a better effect as coarse aggregate. This is because granite is relatively brittle and has a high content of needle-like flakes after crushing, which affects the strength performance of concrete. Diabase has higher hardness and wear resistance, and can provide better durability in concrete, reducing wear and breakage. Moreover, the chemical composition of diabase is usually relatively stable and has good corrosion resistance, which is beneficial to enhancing the durability of concrete.

[0071] From Examples 3, 11-15, it can be seen that the strength and elastic modulus of concrete are better when semi-densified silica fume and original ash are used together. This may be because the original silica fume has fine particles but high water demand and loses slump too quickly, while the particle size of semi-densified silica fume is relatively large but difficult to disperse. The combination of the two can form a particle gradation and fill pores of different sizes, thereby achieving the effect of improving the density of concrete and reasonably controlling the slump. In addition, both original silica fume and semi-densified silica fume have volcanic ash activity, but they differ in the reaction rate and degree with cement hydration products. The combination can play a role at different stages, making the strength development of concrete more uniform and lasting. When the mass ratio of semi-densified silica fume to original ash is 1: (1-3), the compressive strength, elastic modulus, initial crack flexural tensile strength, flexural tensile strength and fracture toughness of concrete are the best.

[0072] It can be seen from Example 3 and Example 16 that by selecting fine aggregate with a fineness modulus of 2.2 to 1.6, the compressive strength, elastic modulus, first crack flexural strength, flexural strength and fracture toughness of concrete are better.

[0073] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A coarse aggregate ultra-high performance concrete, measured by weight, characterized in that: The invention comprises 600-1000 parts of cement, 100-300 parts of silica fume, 100-200 parts of mineral admixture, 10-50 parts of water reducer, 600-1000 parts of fine aggregate, 200-600 parts of coarse aggregate, 50-200 parts of steel fiber and 100-200 parts of water; the coarse aggregate is composed of large coarse aggregate, medium coarse aggregate and small coarse aggregate in a mass ratio of (8-10):(2-3):1, and the particle sizes of the large coarse aggregate, the medium coarse aggregate and the small coarse aggregate satisfy the relationship: Where: a is the particle size of large coarse aggregate, in mm; b is the particle size of medium coarse aggregate, in mm; c is the particle size of small coarse aggregate, in mm; n∈[3,4], and a>b>c≥5; wherein a∈[29,34], b∈[10,12], c∈[5,6].

2. The coarse aggregate ultra-high performance concrete according to claim 1, characterized in that: The fine aggregate is selected from at least one of river sand, quartz sand and machine-made sand, and the fineness modulus of the fine aggregate is 2.2 to 1.

6.

3. The coarse aggregate ultra-high performance concrete according to claim 1, characterized in that: The water-cement ratio of the coarse aggregate ultra-high performance concrete is ≤0.

2.

4. The coarse aggregate ultra-high performance concrete according to claim 1, characterized in that: The coarse aggregate is at least one of diabase and basalt crushed stone.

5. The coarse aggregate ultra-high performance concrete according to claim 1, characterized in that: The silica ash is at least one of fully-densified silica ash, semi-densified silica ash and original ash, and the SiO2 content in the silica ash is ≥94%.

6. The coarse aggregate ultra-high performance concrete according to claim 5, characterized in that: The silica fume is compounded by mixing semi-densified silica fume and original silica fume in a mass ratio of 1:(1-3).

7. The coarse aggregate ultra-high performance concrete according to claim 1, characterized in that: The water reducer is selected from at least one of naphthalenesulfonate water reducer, aminosulfonate water reducer and polycarboxylate water reducer; the steel fiber is selected from at least one of straight steel fiber, end-shaped steel fiber and corrugated steel fiber; the cement is selected from at least one of silicate cement, ordinary silicate cement, slag silicate cement, pozzolanic silicate cement and fly ash silicate cement; the mineral admixture is selected from Subot's model At least one of.

8. Use of the coarse aggregate ultra-high performance concrete according to any one of claims 1 to 7 in bridges and high-rise buildings.

Citation Information

Patent Citations

  • Ultrahigh-performance concrete containing basalt coarse aggregate and preparation method of same

    CN106946520A

  • Low-cost and low-shrinkage coarse aggregate UHPC suitable for cast-in-place and preparation process thereof

    CN113292291A